PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN SELF EFFICACY LEARNING SISWA DI SMA NEGERI 1 SIPIROK - Lisna Agustina (Universitas Muhammadiyah Tapanuli Selatan, 2018)
ABSTRACT The problem in this study is the low self-efficacy learning of students in learning mathematics. To overcome this problem, in this study applied the Learning Learning model. The objectives of this research are: 1) to find out the increase in student self-efficacy learning through the Discovery Learning learning model in SMA 1 Sipirok, 2) to find out the Discovery Learning learning model can increase the activity of students in 1 Sipirok Public High School. quasi experiment. The study population was all students of class X SMA N 1 Sipirok TP. 2017/2018. The sample of this study was the class X MIA-2 students totaling 35 people as the experimental class and the X MIA-4 class totaling 35 people as the control class. Data analysis uses the t-test statistical test, before the data is analyzed first, a data analysis test is conducted, namely the normality and homogeneity test. Based on the results of the calculation of the hypothesis test the value of tcount> ttable or 2.007> 1.667 (with α 0.05), so Ha is accepted and H0 is rejected. This means that there is a significant increase in self efficacy in the experimental class compared to the control class. Keywords: Discovery Learning, Self Efficacy Learning, Student Activities